Pocillopora cryptofauna and their response to host coral mortality - Salas Moya, Carolina (2021)
The cryptofauna are the small cryptic organisms that inhabit the interstices of coral colonies and have a great contribution to the biodiversity of the reef. Some of these species are vulnerable to environmental deterioration due to their dependency on living coral. In the 1990s, Culebra Bay, located in the North Pacific of Costa Rica, was considered one of the most important reef areas in the country, with a mean live coral cover over 40%. However, in the last two decades there was a drastic decrease in live coral cover to 5%, due to El Niño events and recurrent harmful phytoplankton blooms. To evaluate the effect of the deterioration of the reef on the cryptofauna, we compare two time periods: before (2003–2004) and after (2013–2014) coral decline. Pocillopora spp. colonies (~20 cm high by ~20 cm wide) were collected and all associated invertebrates removed. Twenty colonies were sampled each period. During the first period, sampled colonies were alive and healthy, whereas a decade later, exposed skeletons of dead colonies were sampled. A total of 3482 invertebrate individuals were found, belonging to 133 species, 72 families, and nine classes. While abundance and diversity were greater during the 2013–2014 period, we hypothesize that this is due to disturbance intensity being intermediate to high. If these conditions are persistent or intensify over time, however, we expect that once all substrate and reef structure is lost, an abrupt decline in cryptofauna abundance and diversity will take place. Reefs with dead corals therefore have a remarkably different composition of the cryptofauna. Obligate commensal fauna were replaced by boring, opportunistic, and facultative species in these habitats. These changes in live coral cover favored an increase in the diversity of organisms, but this enhanced diversity may be temporary as bioerosion reduces dead colonies to skeleton rubble. This change in the cryptofauna community can affect the recovery and sustainability of the reef ecosystem over time.